The Improvement of Digital Literacy to Secure Data and Privacy in the Digital Age - Francisca Romana Nanik Alfiani; Rineke Sara (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
Digital literacy is essential for navigating online spaces and ensuring safe and effective communication. In today's digital era, personal data and privacy are interconnected concepts crucial for individual rights and protection in an increasingly digital world. This study aims to assess digital literacy and its impact on digital security in Indonesia. The study takes a qualitative approach using descriptive methods, to aimed to answer questions about the state of digital literacy in society and how it can be improved to prevent cybercrime and enhance digital security. The findings can guide policymakers and organizations in promoting digital literacy as a means to enhance overall security.